Brazil in comparative perspective: the legacy of the founding, and the future of constitutional development - Vanzoff Robalinho Cavalcanti, Ana Beatriz (Revista de Investigações Constitucionais, 2019)
This paper analyzes the Brazilian constitutional founding in a comparative perspective, endeavoring to understand how the founding’s identity influenced constitutional development through the three decades since the constitutional document was enacted. By creating a link between the constitutional founding historical and political development and the way the Constitution has changed over time, it hopes to discover more about the evolution and concept of a constitutional identity.